Progress as a paradigm of social and common sense - Shamyakina, Tat’yana I. (Journal of the Belarusian State University. Sociology, 2019)
A modern state of the society, stereotypes and myths of mass consciousness are studied in the form of discussion, in the genre of reflection-analysis. The problems of higher education, its content and formal requirements to it are touched upon. The Bologna regulations’ functioning in higher educational institutions of the Republic of Belarus is considered. The peculiarities of the IT-sphere in Russia and Belarus are highlighted.